TRANSFORMATION OF THE HALAL SYSTEM IN THE INDONESIAN FOOD INDUSTRY IN THE IMPLEMENTATION OF NATIONAL POLICY - Amirudin; Idris Parakkasi; Rahmawati Muin (Yayasan Nuraini Ibrahim Mandiri, 2025)
The transformation of the halal product guarantee system in Indonesia after the enactment of Law No. 33 of 2014 shows the state's commitment to ensuring the protection of Muslim consumers and increasing the competitiveness of the national halal industry. This study uses a descriptive qualitative approach based on literature study to analyze the dynamics of halal policy implementation, especially for Micro, Small and Medium Enterprises (MSMEs). The findings show that although the government has established the Halal Product Guarantee Agency (BPJPH) and launched digital innovations such as SIHALAL and the Free Halal Certification (SEHATI) program, the implementation process still faces structural, technical, and social challenges. Inequality in the distribution of auditors and Halal Examining Institutions (LPH), overlapping authority between BPJPH and MUI, and low halal literacy among MSMEs are the main obstacles. This study emphasizes the importance of cross-institutional synergy, effective communication, empowering business actors, and strengthening human resource capacity and supporting infrastructure to realize an inclusive, credible and sustainable national halal system. The results of this study are expected to be the basis for consideration in the formulation of halal policies that are more adaptive to local conditions and global dynamics.